2022
DOI: 10.3390/gels8010033
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Clove and Cinnamon Supercritical Fluid Extracts-Loaded Emulgel for Antifungal Activity in Denture Stomatitis

Abstract: Denture stomatitis (DS), usually caused by Candida infection, is one of the common denture-related complications in patients wearing dentures. Clove and cinnamon oils have been acknowledged for their anti-inflammatory, antimicrobial activity, and antifungal effects in the oral cavity. The aim of this study, therefore, was to prepare clove/cinnamon oils-loaded emulgel and to assess its efficacy in treating Candida albicans-associated denture stomatitis. Central composite design was adopted to formulate and opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…Since denture stomatitis has high prevalence and recurrence [ 4 , 83 ], many other studies have evaluated drug delivery systems for prevention and treatment of this oral disease [ 79 , 84 , 85 ]. For this, Sultan et al [ 79 ] developed an animal model of denture stomatitis using 3D digital imaging and printing technology to fabricate intraoral devices.…”
Section: Discussionmentioning
confidence: 99%
“…Since denture stomatitis has high prevalence and recurrence [ 4 , 83 ], many other studies have evaluated drug delivery systems for prevention and treatment of this oral disease [ 79 , 84 , 85 ]. For this, Sultan et al [ 79 ] developed an animal model of denture stomatitis using 3D digital imaging and printing technology to fabricate intraoral devices.…”
Section: Discussionmentioning
confidence: 99%
“…Phytomedicine, which has existed since the dawn of human civilization, can be defined as herbal or natural products with therapeutic and medicinal values [ 74 ]. Natural products are said to be effective in treating DS because they have improved the clinical and microbiological aspects of the condition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the incorporation of natural products into the acrylic resin denture base material might be effective in preventing Candida albicans adhesion. Compared to traditional antifungals, these products have a better taste, comparable efficacy, fewer side effects, and higher patient satisfaction [ 45 , 65 , 74 ]…”
Section: Discussionmentioning
confidence: 99%
“…Their use implies lower toxicity compared to oral or intravenous antifungals, excellent chemical stability, and enhanced penetration in infected areas, making them effective delivery agents for multiple compounds [ 55 ]. The benefits of plant-extract-based gels have been observed in emulgels loaded with clove/cinnamon oils, which are an alternative for treating C. albicans -associated denture stomatitis [ 56 ], and in hydrogels integrating lemongrass-loaded nanosponges showing an enhanced antifungal effect with reduced irritation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%